Malignant Pleural Mesothelioma: State-of-the-Art on Current Therapies and Promises for the Future - Nicolini, Fabio; Bocchini, Martine; Bronte, Giuseppe; Delmonte, Angelo; Guidoboni, Massimo; Crinò, Lucio; Mazza, Massimiliano (Frontiers in Oncology, 2020)
Malignant pleural mesothelioma (MPM) is a rare, aggressive cancer of the pleural surface associated with asbestos exposure. The median survival of MPM patients is of mere 8-14 months and there are few biomarkers and no cure available. It is hoped that eventually the incidence of MPM will drop and remain low and constant, given that most nations have banned the use of asbestos, but in the meantime, the incidence in Europe is still growing. The exact molecular mechanisms that explain carcinogenicity of asbestos are not known. Standard therapeutic strategies for MPM include surgery, often coupled with chemotherapy and/or radiotherapy, in a small percentage of eligible patients and chemotherapy in tumours considered unresectable with or without adjuvant radiotherapy. In recent years, several new therapeutic avenues are being explored. These include: angiogenesis inhibitors, synthetic lethal treatment, miRNA replacement, oncoviral therapies and the fast-growing field of immunotherapy alone or in combination with chemotherapy. Of particular promise are the multiple options offered by immunotherapy: immune checkpoint inhibitors, tumour vaccines and therapies taking advantage of tumour-specific antigens, such as specific therapeutic antibodies or advanced cell-based therapies exemplified by the CAR-T-cells. This review comprehensively presents both old and new therapeutic options in MPM focusing on the results of the numerous recent and on-going clinical trials in the field, including last data presented at international meetings (AACR, ASCO and ESMO) this year, and concludes that more work has to be done in the framework of tailored therapies to identify reliable targets and novel biomarkers to impact on MPM management.